Legal Re-Construction; The Impact of Empty Column Victory Over Single Candidates in Simultaneous Direct Elections of Regional Heads as A New Phenomenon of Legal Politics in Indonesia : (Case Study: Makassar City) - Jaya, Apriliani Kusuma; Ilyas, Ilyas (IJBLE Scientific Publications Community Inc., 2024)
This study examines the legal re-construction of the victory impact of an empty column over a single candidate as a new phenomenon of legal politics in Makassar City, South Sulawesi, Indonesia. This is a doctrinal normative legal research, which uses the analytical, explorative, explanatory, and qualitative analysis techniques. The result showed that legal reconstruction needs to be carried out on disputes, policies of single candidate pairs and empty columns, nomination requirements and political party support for candidates. The legal construction also needs to be conducted on the phrase